The Influence of Thin Capitalization, Capital Intensity and Sales Growth on Tax Avoidance with Institutional Ownership as a Moderating Variable in Manufacturing Companies Registered as Indonesian Sharia Stock Index Companies - Ayuningtia, Miranda; Pramiana, Omi (International Journal of Pertapsi, 2024)
This research aims to determine the effect of thin capitalization, capital intensity and sales growth on tax avoidance with institutional ownership as a moderating variable in manufacturing companies listed as Indonesian sharia stock index companies in 2021-2022. This research uses a quantitative descriptive method, with a total sample of 52 companies with 104 data used obtained from the company's annual financial reports. The results of this research show that thin capitalization, capital intensity, sales growth has an effect on tax avoidance, institutional ownership is able to moderate the effect of thin capitalization on tax avoidance, institutional ownership is able to moderate the effect of capital intensity on tax avoidance and institutional ownership unable to moderate the influence of sales growth on tax avoidance.